2013
DOI: 10.1167/iovs.12-10097
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity and Specificity of Short-Duration Transient Visual Evoked Potentials (SD-tVEP) in Discriminating Normal From Glaucomatous Eyes

Abstract: Short-duration transient VEP objectively identified decreased visual function and discriminated between healthy and glaucomatous eyes, and also showed good differentiation between healthy eyes and those with early visual field loss. VEP may be useful for early diagnosis of glaucoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 23 publications
1
13
0
Order By: Relevance
“…The ss‐PERG is known to specifically represent the function of the RGCs themselves, and RGCs are damaged in the pathophysiology of glaucoma . SD‐tVEP is a measure of a function of the entire visual pathway from the photoreceptors to the visual cortex and therefore may not be as sensitive to dysfunction of the RGCs themselves …”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The ss‐PERG is known to specifically represent the function of the RGCs themselves, and RGCs are damaged in the pathophysiology of glaucoma . SD‐tVEP is a measure of a function of the entire visual pathway from the photoreceptors to the visual cortex and therefore may not be as sensitive to dysfunction of the RGCs themselves …”
Section: Discussionmentioning
confidence: 99%
“…A study by Parisi et al found that an increased P100 latency of transient VEP had a sensitivity and specificity of 100% for detecting glaucoma. 24,25,32 The difference in SD-tVEP results between the two studies may be explained by differing study populations, study designs, levels of disease severity among tested patients or the reduced sample size after applying exclusion criteria.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations